A study on construction using cofferdam method in coastal area case study: Kota Kinabalu City / Rafflesia Sombuling - Sombuling, Rafflesia (2015)
This paper presents an overview of the present state of construction of cofferdam techniques with special emphasis and a brief on other techniques developed world over for mitigating hydraulic forces on the temporary structures.A cofferdam is a temporary structure designed to keep water and soil out of the excavation in which a bridge pier or other structure is built. When construction must take place below the water level, a cofferdam is built to give workers a dry work environment.Sheet piling is driven around the work site, seal concrete is placed into the bottom to prevent water from seeping in from underneath the sheet piling, and the water is pumped out. There are different types of cofferdam, some are used to support excavation operation and some are enclosed type box placed in the water.The present case study deals with step by step procedure adopted at Sabah International Convention Centre and Jesselton Residence which is both located at Kota Kinabalu Sabah. It depicts the intricacy of the management of the work at site and gives lot of insights to such similar works involving details of bentonite slurry, rock bund, planning and execution of interlocking sheet piles, reinforcement, concreting, plants and equipment, safety procedures to be adopted for the construction of cofferdam.